PENGEMBANGAN AGRIBISNIS DALAM RANGKA PEMBANGUNAN EKONOMI LOKAL DI KABUPATEN KAPUAS, KALIMANTAN TENGAH - Syaukat, Yusman (Jurnal Manajemen Pembangunan Daerah, 2009)
Agribusiness and local economic development have a close connection. Agricultural development through agribusiness approach has proven to improve local economic development in many countries: increase added value and income of farmers, and create job opportunities for the people. Main commodities grown in Kapuas District, Province of Central Kalimantan are rice, rubber, and fish and livestock products. However, those commodities have not yet developed according to agribusiness principals, since most of them are sold as raw materials, thus the region losses its economic potential from processing those products. The objective of this paper is to explore agribusiness development strategy in Kapuas Regency to be able to contribute to local economic development. To meet this objective, agribusiness in Kapuas Regency should be based on local condition and resources, by considering local agro-ecosystem, social principal (fairness, democracy), economic principal (market oriented, competitiveness, added value, and job opportunity), and supported by sufficient local government policy through institutional, technology and capital development.Keyword: agribusiness, local economy development, competitiveness, added value, Kapuas regency.